Pengaruh Aplikasi Karbamid Peroksida 20% Dan 35% Terhadap Kekerasan Resin Komposit Mikro Hibrid - Dewi Liliany Margaretta; Vega Indriana (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: Many people are very concerned about performance especially in terms of the appearance of their teeth. Various attempts were made to improve the appearance of teeth by bleaching. Carbamide peroxide and hydrogen peroxide as bleaching materials may release free radicals which affect surface roughness of the composite restoration. Objective: to determine the effect of carbamide peroxide 20% and 35% on micro hybrid resin composite hardness Methods: Samples are micro hybrid resin composite with 4 mm thickness and 10 mm diameter. Total number is 10 samples for each groups which were divided into 2 groups: group 1 application of 20% carbamide peroxide and group 2 application of 35% carbamide peroxide. Each group were tested prior, after 7 and 14 days using Vickers Hardness. Result: The results indicate that there was no significant effect of 20% carbamide peroxide on resin composite hardness for 7 days with (p > 0.05) and 35% for 7 days (p > 0.05), but the use of carbamide peroxide 20% and 35% on a micro hybrid resin composite for 14 days yielded a significant increase in hardness (p<0.01). Conclusion: The use of carbamide peroxide 20% and 35% for 7 and 14 days did not cause hardness decrease on micro hybrid resin composite.